1995
DOI: 10.1021/bi00033a015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rat C-Reactive Protein and Other Pentraxins with Rat Lipoproteins Containing Apolipoproteins E and A1

Abstract: C-Reactive protein (CRP) is a member of the pentraxin family of proteins, ubiquitous components of animal serum. This study suggests that, in serum, rat CRP is complexed with lipoprotein and may interact directly with apolipoprotein E. When mixed with diluted rat serum, radiolabeled rat CRP showed a slightly higher sedimentation coefficient (about 15%) than that of the free protein. Elimination of calcium or addition of O-phosphorylethanolamine (O-PE), a low molecular weight compound that binds tightly to rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…27 Meanwhile, a recent study suggested that the contribution of the e4 allele towards lowering CRP levels is independent and may be by a different mechanism than how statins affect inflammation. 19 However, implication of lipoprotein pathway of the cholesterol transport remained plausible since Schwalbe et al 28 reported that CRP may be complexed with lipoprotein by a direct interaction with the apolipoprotein E molecule, suggesting a direct effect of the APOE e4 allele on hs-CRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…27 Meanwhile, a recent study suggested that the contribution of the e4 allele towards lowering CRP levels is independent and may be by a different mechanism than how statins affect inflammation. 19 However, implication of lipoprotein pathway of the cholesterol transport remained plausible since Schwalbe et al 28 reported that CRP may be complexed with lipoprotein by a direct interaction with the apolipoprotein E molecule, suggesting a direct effect of the APOE e4 allele on hs-CRP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…2003). In addition, in a rodent model system it has been proposed (Schwalbe et al 1995) that CRP is complexed with lipoprotein, and may interact directly with apolipoprotein E. Austin et al . (2004) speculated that, given the half‐life of plasma CRP if lipoprotein‐bound‐CRP versus free CRP has a different rate of clearance, CRP concentrations in individuals with different APOE genotypes may be a consequence of the slower VLDL clearance in apoE2, and faster clearance in apoE4, subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, CRP was shown to interact with serum components containing apolipoproteins E and A1. 32 The interaction is Ca Ï©Ï© dependent and is inhibited by O-phosphorylethanolamine, a compound that tightly binds specifically to rat CRP. Bhakdi et al 33 showed that when LDL is modified by exposure to a combination of trypsin, cholesterol esterase, and neuraminidase, it binds CRP and has complement-activating activity.…”
Section: Crp-vldl Complex and Dic 2527mentioning
confidence: 99%